ANALISIS SISTEM INFORMASI AKUNTANSI DALAM PENGENDALIAN KUALITAS PRODUK PADA BAGIAN QUALITY CONTROL PT. ABC - Putri Aulia Tama; Indra Cahya Kusuma; M. Nur Afif (Komunitas Manajemen Kompetitif, 2026)
This research aims to analyze the application of the Accounting Information System (AIS) in supporting product quality control in the Quality Control (QC) section of PT. ABC is based on the Committee of Sponsoring Organizations of the Treadway Commission (COSO) framework. The research method used is a descriptive qualitative approach with data collection techniques through observation, interviews and documentation. The research results show that the implementation of the COSO-based Internal Control System (SPI) in product quality control has generally gone well. The components of the control environment, control activities, information and communication, and monitoring activities are considered to be in accordance with COSO theory, while the risk assessment component is not yet fully optimal because identification and management of quality risks are still reactive and have not been documented systematically. The application of AIS plays an important role in providing relevant and accurate information to support decision making, strengthen coordination between units, and help reduce the level of product defects. It is hoped that this research can provide theoretical contributions in the development of COSO-based SIA and SPI studies as well as become practical consideration for companies in increasing the effectiveness of product quality control in the garment industry. Keywords: Accounting Information System, Product Quality Control, COSO, Quality Control